2008
DOI: 10.1074/jbc.m801041200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Functional Interference of Glucocorticoid Receptor and SOCS1

Abstract: Cytokine and glucocorticoid (GC) hormone signaling act in an integrated fashion to control inflammation and immune response. Here we establish a new mode of interaction of these two pathways and propose Suppressor of Cytokine Signaling (SOCS)-1 as an essential player in mediating cross-talk. We observed that glucocorticoid receptor (GR) and SOCS1 form an intracellular complex through an interaction, which required the SH2 domain of SOCS1 and the ligand binding domain of GR. Furthermore, GC stimulation was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Induction of SOCS Family Member in Response to IL-4 and IL-13 Stimulation-Previous studies found that the SOCS family of proteins is critical for regulating M2 development (42,43,45,48,49) and IRS-1 signaling in response to insulin (47,50,51). Based on our findings that IL-4-induced IRS-2 signaling is rapidly turned on within 30 min and turned off by 180 min, we sought to define whether SOCS family members are involved in this negative regulatory process.…”
Section: Kinetics Of Irs-2 Tyrosine Phosphorylation In Response Tomentioning
confidence: 99%
“…Induction of SOCS Family Member in Response to IL-4 and IL-13 Stimulation-Previous studies found that the SOCS family of proteins is critical for regulating M2 development (42,43,45,48,49) and IRS-1 signaling in response to insulin (47,50,51). Based on our findings that IL-4-induced IRS-2 signaling is rapidly turned on within 30 min and turned off by 180 min, we sought to define whether SOCS family members are involved in this negative regulatory process.…”
Section: Kinetics Of Irs-2 Tyrosine Phosphorylation In Response Tomentioning
confidence: 99%
“…Proteins from total cell extracts were separated on 8% SDS-PAGE and immunoreactive bands detected and quantified by Odyssey Infrared Imaging (LICOR, Biosciences) as described (Haffner et al, 2008). STAT1 immunohistochemistry was performed on paraffin-embedded sections with SC-346 antibody (Santa Cruz Biotechnology; 1:1000, 1hr R.T.) and the Rabbit-on-Rodent HRP-Polymer (Biocare Medical) as a secondary detection system.…”
Section: Immunoblotting Imunohistochemical Analysismentioning
confidence: 99%
“…Haffner et al 22 observed that glucocorticoid receptor and SOCS1 form an intracellular complex by immunoprecipitation and appeared to increase the nuclear expression level of SOCS1. Cortisol treatment significantly elevated SOCS1 mRNA transcript levels in rainbow trout liver.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Glucocorticoids suppresses inflammation by controlling and preventing the immune-correlated damages. The upregulation of SOCS1 by corticosteroids has been established both in vivo and in vitro, [22][23][24] which suggests that cortisol may be playing a key role in suppressing cytokine signaling and the associated inflammatory response through SOCS1. However, the effect of glucocorticoid on SOCS1 remains unclear in ACHBLF.…”
mentioning
confidence: 99%